(untitled) (Bangladesh Journal of Botany, 2024)
This study aims to identify the pathogen causing wilt disease of Chinese yam (Dioscorea polystachya Turczaninow.) in Hunan Province. Diseased stems were collected from the fields in Loudi City in the Hunan Province. Tissue culture method was used for the isolation of the pathogen causing wilt disease of Chinese yam, and was identified as Fusarium asiaticum based on the morphological characteristics and molecular technology. Out of five fungicides, Difenoconazole· Azoxystrobin 40% SC, Hexaconazole 5% SC, and Difenoconazole 10% WDG, demonstrated inhibitory effects on the pathogen. Among them, hexonazole 5% SC had the lowest EC50 value and was the most sensitive to the pathogen of Chinese yam wilt, so it should be selected first for the control of Chinese yam wilt. Bangladesh J. Bot. 53(3): 857-863, 2024 (September) Special